Transition‐Metal‐Controlled Inorganic Ligand‐Supported Non‐Precious Metal Catalysts for the Aerobic Oxidation of Amines to Imines. Issue 56 (12th September 2017) - Yu, Han; Zhai, Yongyan; Dai, Guoyong; Ru, Shi; Han, Sheng; Wei, Yongge
Abstract: Most state‐of‐art transition‐metal catalysts usually require organic ligands, which are essential for controlling the reactivity and selectivity of reactions catalyzed by transition metals. However, organic ligands often suffer from severe problems including cost, toxicity, air/moisture sensitivity, and being commercially unavailable. Herein, we show a simple, mild, and efficient aerobic oxidation procedure of amines using inorganic ligand‐supported non‐precious metal catalysts 1, (NH4 ) n [MMo6 O18 (OH)6 ] (M=Cu 2+ ; Fe 3+ ; Co 3+ ; Ni 2+ ; Zn 2+, n =3 or 4), synthesized by a simple one‐step method in water at 100 °C, demonstrating that the catalytic activity and selectivity can be significantly improved by changing the central metal atom. In the presence of these catalysts, the catalytic oxidation of primary and secondary amines, as well as the coupling of alcohols and amines, can smoothly proceed to afford various imines with O2 (1 atm) as the sole oxidant. In particular, the catalysts 1 have transition‐metal ion core, and the planar arrangement of the six Mo VI centers at their highest oxidation states around the central heterometal can greatly enhance the Lewis acidity of catalytically active sites, and also enable the electrons in the center to delocalize onto the six edge‐sharing MO6 units, in the same way as ligands in traditional organometallic complexes. The versatility of this methodology maybe opens a path to catalytic oxidation through inorganic ligand‐coordinated metal catalysis. Abstract : A breath of fresh air : A mild aerobic oxidative coupling protocol of primary and secondary amines as well as the coupling of alcohols and amines to afford corresponding imines was developed with inorganic ligand‐supported metal catalyst (NH4 ) n [MMo6 O18 (OH)6 ] (M=Cu 2+, Fe 3+, Co 3+, Ni 2+, Zn 2+ ). This method utilizes mainly an inorganic polymolybdate ligand to support the Cu 2+ ion and 1 atm O2 gas as the sole oxidant, which can smoothly proceed to afford various imines in high yields and selectivity, avoiding the use of expensive, toxic, air/moisture sensitive, and commercially unavailable organic ligands.